Analisis Bahan Ajar Al-Quran Hadist Di Sekolah Menengah Pertama - Ayunda, Hasnirda; Rahmadhani, Riri; Fadriati, Fadriati (Innovative: Journal Of Social Science Research, 2024)
This study uses a qualitative method with a Literature Review approach to analyze various sources of literature on the method of learning the Qur'an and Hadith in Junior High Schools (SMP). The focus of this study is on the aspects of planning, implementing, and evaluating integrative learning of the Qur'an and Hadith. The results of the study indicate that learning planning must include clear learning objectives, appropriate methods, and the use of media that are relevant to student characteristics. At the implementation stage, the teacher acts as a facilitator who encourages active student involvement, while integrative learning connects the teachings of the Qur'an and Hadith with students' daily lives. Various learning strategies, such as direct, interactive, and experience-based learning, are applied to achieve holistic educational goals, covering cognitive, affective, and psychomotor aspects. Learning evaluation is carried out using a comprehensive method, aiming to determine learning achievements, provide feedback, and plan corrective actions. This evaluation is important to improve students' understanding and ability to practice the values ​​of the Qur'an and Hadith in everyday life.